2021
DOI: 10.1051/metal/2020089
|View full text |Cite
|
Sign up to set email alerts
|

The influence of carbonitriding conditions on microstructure and mechanical properties of 25CrMo4 low-alloy steel

Abstract: Carbonitriding is an important industrial process applied for the improvement of the mechanical characteristics of the component of many steels employed in several machines parts like cam shafts, crank shafts and gears to enhance fatigue strength and wear resistance. In this study, the influence of the gaseous carbonitriding on the enhancement of surface characteristics and mechanical properties was investigated using different parameters for low alloy steel. The analysis and characterization of the treated ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This layer is composed of martensitic needles comprising Fe3C carbides and retained austenite. 8 The XRD graph of carbonitrided AISI 4130 low alloy steel at different carbon concentrations are shown in Figure 4. Although the structure consisted of austenite phase, ε(Fe23CN), γ(Fe4N), and chromium nitride precipitates were observed in the carbonitrided samples depending on carbonitriding parameters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This layer is composed of martensitic needles comprising Fe3C carbides and retained austenite. 8 The XRD graph of carbonitrided AISI 4130 low alloy steel at different carbon concentrations are shown in Figure 4. Although the structure consisted of austenite phase, ε(Fe23CN), γ(Fe4N), and chromium nitride precipitates were observed in the carbonitrided samples depending on carbonitriding parameters.…”
Section: Resultsmentioning
confidence: 99%
“…11 In this regard, several studies have been conducted on the microstructural and mechanical properties of carbonitriding treatment, using plasma 12 and gas carbonitriding. 8 Thi Chieu et al 13 found that the microhardness of carbonitriding SCM420 was enhanced from 40 HRC for the untreated material to 65 HRC. In addition, Hoja et 14 found that the carbonitriding treatment improved the wear resistance of forging dies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heat treatment of experimental cast steel adopts a simple process of normalizing + high‐temperature tempering. [ 17 ] The sample is put into a box‐type resistance furnace filled with nitrogen, heated to 880 °C for 1 h, cooled in air to room temperature, then tempered within 520–650 °C, kept for 1.5 h, and air‐cooled to room temperature.…”
Section: Methodsmentioning
confidence: 99%